The eclipsing LMC star OGLE05155332-6925581: a clue to understand Double Periodic Variables - Mennickent, R. E. (2008)
We investigate the nature of OGLE05155332-6925581, one of the brightest members of the enigmatic group of double periodic variables (DPVs) recently found in the Magellanic Clouds. The modelling of archival orbital light curves (LCs), along with the analysis of the radial velocities (RVs) suggest that this object is a semidetached binary with the less massive star transferring matter to the more massive and less evolved star, in an Algol-like configuration. We find evidence for additional orbital variability and Hα emission, likely caused by an accretion disc around the primary star. As in the case of βLyr the circumprimary disc seems to be more luminous than the primary, but we do not detect orbital period changes. We find that the LC follows a loop in the colour-magnitude diagram during the long cycle; the system is redder when brighter and the rising phase is bluer than during decline. Infrared excess is also present. The source of the long-term periodicity is not eclipsed, indicating its circumbinary origin. Strong asymmetries, discrete absorption components (DACs) and a γ shift are new and essential observational properties in the infrared HI lines. The DACs strength and RV follow a saw-teeth pattern during the orbital cycle. We suggest that the system experiences supercycles of mass outflow feeding a circumbinary disc. Mass exchange and mass loss could produce comparable but opposite effects in the orbital period on a long time-scale, resulting in a quasi-constancy of this parameter.